Association between NT-proBNP level and the number of stents with major advanced cardiovascular events (MACE) in patients with multivessel coronary artery disease treated with percutaneous coronary intervention: A prospective cohort study - Subkhan, Muhammad; Heriansyah, Teuku; Munirwan, Haris; Purnawarman, Adi; Dimiati, Herlina (Narra Sains Indonesia, 2024)
Complex revascularization strategies, particularly complete revascularization, are controversial in coronary artery disease (CAD), and data supporting routine revascularization in stable CAD is lacking. The importance of percutaneous coronary intervention (PCI) in CAD and N-terminal pro-brain natriuretic peptide (NT-proBNP), which has been studied as a predictor of major advanced cardiovascular events (MACE) in CAD patients, still requires further research. The aim of this study was to determine the association between NT-proBNP levels and the number of stents with MACE incidence in CAD cases. A prospective cohort study was conducted in both types of CAD (acute coronary syndrome (ACS) and chronic coronary syndrome (CCS)). The NT-proBNP levels were measured pre- and post-PCI using fluorescence immunoassay, while MACE was assessed three months post-PCI. The Student t-test was used to compare the levels of NT-proBNP between pre- and post-PCI and between those who had MACE and did not; both in patients treated with single or multiple stenting groups. A total of 32 CAD patients were recruited, consisting of 20 ACS cases and 12 CCS cases. NT-proBNP levels post-PCI increased significantly in both ACS and CCS patients compared to pre-PCI either among those treated with single and multiple stentings. MACE occurred in 4 (12.5%) out of a total of 32 patients, all of which occurred in ACS patients treated with multiple stentings. Those who had MACE had higher post-PCI NT-proBNP levels compared to those who did not have MACE (23,703.50 vs 11,600.17 pg/mL, p=0.013). This study highlights the association between elevated NT-proBNP levels and multiple stenting with the presence of MACE in CAD patients, particularly in ACS cases.